Long‐term outcomes in Japanese nonagenarians undergoing transcatheter aortic valve implantation: A multi‐center analysis. Issue 6 (23rd April 2019) - Yokoyama, Hiroaki; Tobaru, Tetsuya; Muto, Yuki; Hagiya, Kenichi; Higuchi, Ryosuke; Saji, Mike; Takamisawa, Itaru; Shimizu, Jun; Takanashi, Shuichiro; Takayama, Morimasa; Tomita, Hirofumi; Tamura, Harutoshi; et al.
Abstract: Background and Hypothesis: Japan is an aging society, and the number of nonagenarians with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI) is increasing, but their outcomes have not been determined fully. Methods: We prospectively enrolled 767 consecutive patients who underwent TAVI in three Japanese institutions. Clinical characteristics and outcomes of nonagenarians (n = 94) were evaluated and compared with those of patients aged <90 years (n = 673). Results: Prevalence of New York Heart Association (NYHA) class III/IV was not different between the two groups. Preoperative risk scores were significantly higher in nonagenarians compared with those in non‐nonagenarians, whereas the Clinical Frailty Scale was not different. Thirty‐day mortality tended to be higher ( P = .06) and major vascular complication was significantly higher in nonagenarians than in non‐nonagenarians ( P < .05), but 3‐year mortality was equivalent between the two groups. Even after adjustment for covariates, female sex (hazard ratio, 0.41; 95% confidence interval: 0.25‐0.67), body mass index (0.87, 0.80‐0.94), and NYHA class III/IV (1.84, 1.06‐3.29) were associated with all‐cause mortality. Age ≥ 90 years was not associated with all‐cause mortality. Conclusions: TAVI could be undertaken safely and effectively in nonagenarians, who had acceptable long‐term results compared with those for younger patients, although careful attention should be paid to major vascular complication.